A two-step immunoassay for the simultaneous assessment of Aβ38, Aβ40 and Aβ42 in human blood plasma supports the Aβ42/Aβ40 ratio as a promising biomarker candidate of Alzheimer’s disease - Hedieh Shahpasand-Kroner; Hans-W. Klafki; Chris Bauer; Johannes Schuchhardt; Melanie Hüttenrauch; Martina Stazi; Caroline Bouter; Oliver Wirths; Jonathan Vogelgsang; Jens Wiltfang (Alzheimer’s Research & Therapy, 2018)
Abstract Background The quantification of amyloid-beta (Aβ) peptides in blood plasma as potential biomarkers of Alzheimer’s disease (AD) is hampered by very low Aβ concentrations and the presence of matrix components that may interfere with the measurements. Methods We developed a two-step immunoassay for the simultaneous measurement of the relative levels of Aβ38, Aβ40 and Aβ42 in human EDTA plasma. The assay was employed for the study of 23 patients with dementia of the Alzheimer’s type (AD-D) and 17 patients with dementia due to other reasons (OD). We examined relationships with the clinical diagnosis, cerebral Aβ load as quantified by amyloid-positron emission tomography, apolipoprotein E genotype, Aβ levels and Tau protein in cerebrospinal fluid. Results Preconcentration of plasma Aβ peptides by immunoprecipitation substantially facilitated their immunological measurements. The Aβ42/Aβ40 and Aβ42/Aβ38 ratios were statistically significantly lower in the AD-D patients than in the OD group. The areas under the receiver operating characteristic curves reached 0.87 for the Aβ42/Aβ40 ratio and 0.80 for the Aβ42/Aβ38 ratio. Conclusions The measurement of plasma Aβ peptides with an immunological assay can be improved by preconcentration via immunoprecipitation with an antibody against the Aβ amino-terminus and elution of the captured peptides by heating in a mild detergent-containing buffer. Our findings support the Aβ42/Aβ40 ratio in blood plasma as a promising AD biomarker candidate which correlates significantly with the validated core biomarkers of AD. Further studies will be needed for technical advancement of the assay and validation of the biomarker findings.